“INTEGRASI PASAR KEUANGAN INTERNASIONAL DAN NILAI TUKAR: SUATU STUDI LITERATUR KOMPREHENSIF" - Yustia Dewi; Sonang Matua Siregar; Khaidar Rahmaini Jamila (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The increasing integration of international financial markets has reshaped exchange rate dynamics and strengthened their linkage with global financial market movements. This study aims to comprehensively examine the relationship between international financial market integration and exchange rates through a literature-based approach. A semi-systematic literature review method is employed by analyzing five reputable scholarly journal articles relevant to the research topic. The synthesis of findings indicates that greater financial market integration heightens exchange rate sensitivity to external factors and positions exchange rates as a key component in the transmission mechanism of global financial shocks. Despite differences in research contexts and analytical approaches, the literature consistently highlights a strong and dynamic relationship between these two variables. This study contributes to a deeper conceptual understanding and structured mapping of the literature on the role of exchange rates within an increasingly integrated global financial system.